(untitled) (Academia Science Repository, 2023)
This article describes the main work performed on the restoration and repair of emerging shaft malfunctions. Shafts are the main parts of internal combustion engines and various equipment. Shafts are used to convert and transmit torque, gears, pulleys, half couplings.